Changes in folic acid, phenolic components, and angiotensinconverting enzyme inhibitory activity in cowpea (Vigna unguiculata) green pods with different pod maturity - Ishikawa, H.; Matsumoto, R.; Iseki, K. (SAGE Publications, 2025)
Objective: Cowpea is an important dry bean in developing countries, and its young leaves and green pods are consumed as fresh vegetables. Consuming green pods provides vitamins, minerals, and functional components for small-scale farmers with limited access to vegetables. However, the accumulation process of functional components in young cowpea pods is unknown. Therefore, we evaluated the concentrations of folic acid, phenolic components, and angiotensin-converting enzyme (ACE) inhibitory activity in green pods throughout maturity to determine the accumulation process of functional components. Methods: Four cowpea genotypes were selected from a mini-core subset of the world cowpea germplasm collection based on protein content, seed size, and seed coat color. The accumulation process of functional components in young cowpea pods was evaluated by measuring the concentrations of folic acid, phenolic components, and ACE inhibitory activity in green pods throughout pod growth (10 days after flowering (DAF): pod elongated, 15 and 20 DAF: seed growth, and 25 DAF: ready for harvest). Results: Our results demonstrate that consuming green cowpea pods during the early growth stages (10–15 DAF) can simultaneously provide a high content of dual nutrition, folic acid, and phenolic components. In addition, the pod had high ACE inhibitory activity. Folic acid and phenolic components were highest in the early stages of 10 DAF, whereas ACE inhibitory activity remained constant during 10–25 DAF. Conclusion: Our findings suggest that including green cowpea pods in diets can boost folic acid and phenolic component intakes without disrupting the ACE inhibitory activity. Furthermore, underutilized genetic resources featuring colored seeds would enhance the nutritional value of cowpeas in breeding programs, thereby increasing the nutritional benefits derived from cowpea consumption.